The practice of English language teaching - Harmer, Jeremy (Pearson Longman, 2007)
In this new edition, Jeremy Harmer brings you: the evolving identities of global English; The impact of technology on teaching; The issue of context-sensitive methodology; DVD with clips from real classrooms, observation tasks and interviews.